Rebuilding Children's Love of Traditional Game in Order to Grow it - Salsabila Deona (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
Playing is something that can’t be realeased by children this activity they do almost every day. In this modern era, games played by children are increasingly sophisticated. So that the traditional game began to be forgotten. In fact, in terms of health, traditional games help more children in their growth and development. Children are in the golden age, at the age the physical and brain of the child are in a period of very rapid development. Therefore by playing traditional games can improve and help the children's physical and brain growth and development.Keywords: Traditional Games, Children, Growth and Development